Review and characterization of the 2014 Orkney damage datasets for damage pattern mapping and fragility curve construction - Nqasha, Thando; Akombelwa, Mulemwa; Singh, Mayshree; Kijko, Andrzej (Frontiers in Built Environment, 2025)
The 2014 Orkney earthquake caused significant damage to unreinforced masonry buildings in the surrounding townships. After the earthquake, field surveys were conducted to assess the extent of damage in the affected areas. This study reviews data collected from the 2014 Orkney earthquake to investigate damage patterns, evaluate building safety for occupancy, and support fragility curve construction. Damage was quantified based on the European Macroseismic Scale (EMS-98) to assess building safety and conduct regression analysis. The results indicate that the collected data is suitable for investigating damage patterns and determining building safety for occupancy. However, it is not suitable for constructing fragility curves. Empirical fragility curves are typically developed using logistic regression, but this study found the data unsuitable for regression analysis due to sampling errors and limited data quantity. This study recommends the use of first-order approximation methods to supplement the dataset, reducing sampling errors and increasing data quantity.